Are Physical Activity and Sedentary Screen Time Levels Associated With Food Consumption in European Adolescents? The HELENA Study. Issue 1 (2nd January 2023) - Moradell, Ana; Santaliestra-Pasías, Alba M.; Aparicio-Ugarriza, Raquel; Huybrechts, Inge; Bertalanné Szommer, Aliz; Forsner, Maria; González-Gross, Marcela; Kafatos, Anthony; Androutsos, Odysseas; Michels, Nathalie; Sjöström, Michael; Vanhelst, Jeremy; et al.
Abstract: Objective : One of the current main public health problems is the prevalence of obesity in children. Unhealthy lifestyle behaviors such as poor dietary habits, high sedentary screen time (SST), and low levels of physical activity (PA) have a strong tendency to track from childhood into adulthood. The aim of this manuscript is to assess the association between meeting or not meeting the PA and SST recommendations and the consumption of different food groups. Method : Data were obtained from a sample of European adolescents from the multicenter cross-sectional HELENA study. In all, 1448 adolescents from 8 cities were included. PA was objectively measured by accelerometry and dietary intake by 24-hour dietary records. Adolescents were grouped according to PA and SST recommendations. Results : In both sexes, intake of savory snacks was higher in those groups who did not meet any of the recommendations ( p < 0.05). For males, those who met both recommendations were more likely to drink/eat milk, yogurt, and water ( p < 0.05). Those not meeting recommendations were more likely to drink sugar-sweetened beverages ( p < 0.05). For females, those not meeting recommendations were less likely to eat fruits and vegetables and more likely to have a higher intake of fats and oils ( p < 0.05). Conclusions : Those adolescents meeting PA and SST recommendations had a higher intake of healthy foods, like fruit and vegetables and dairy products. However, the negative relationship unhealthier food and SST is stronger in males independently of PA. More studies assessing the combined effect of both PA and SST regarding dietary habits in children and adolescents are needed.